2020
DOI: 10.1186/s12891-020-03489-7
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-410-3p modulates chondrocyte apoptosis and inflammation by targeting high mobility group box 1 (HMGB1) in an osteoarthritis mouse model

Abstract: Background: Osteoarthritis (OA) is the most prevalent type of arthritis, which commonly involves inflammation in the articular cartilage in OA pathogenesis. MicroRNAs (miRNAs) play essential roles in the regulation and pathophysiology of various diseases including OA. MiR-410-3p has been demonstrated to mediate inflammatory pathways, however, the regulatory functions of miR-410-3p in OA remain largely unknown. Methods: The regulations of miR-410-3p were investigated in OA. Mouse primary chondrocytes and mouse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 57 publications
2
18
0
Order By: Relevance
“…HMGB1 is an alarmin present in the extracellular environment after chondrocyte or macrophage pyroptosis (death). Actually, this protein is a target in the development of miRNA therapies for OA [50], as early protein blockade can decrease cartilage deterioration [51]. Current predictions revealed that PRP influences HMGB1 signaling.…”
Section: Discussionmentioning
confidence: 99%
“…HMGB1 is an alarmin present in the extracellular environment after chondrocyte or macrophage pyroptosis (death). Actually, this protein is a target in the development of miRNA therapies for OA [50], as early protein blockade can decrease cartilage deterioration [51]. Current predictions revealed that PRP influences HMGB1 signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Hierarchical clustering of the 60 identi ed miRNA pro les highlighted that the patterns characterizing the patients with anti-gp210 positive PBC differed from those characterizing the patients with anti-gp210 negative PBC, suggesting that some miRNAs may be involved in the production of anti-gp210 antibodies, and even the clinical progression of PBC, or that some cases may progress as a result of speci c changes in the expression of some miRNAs. We suspected that these miRNAs might play important roles in the disease process, and we focused on one potentially important miRNA, miR-410-3p, which had previously been reported in autoimmune diseases including rheumatoid arthritis, osteoarthritis and various cancers [10,23,24]. We found that expression of miR-410-3p changed signi cantly: real-time PCR con rmed that miR-410-3p in serum from patients with anti-gp210 antibodies positive PBC showed higher expression in comparison with the patients with anti-gp210 antibodies negative PBC and healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…These data indicate that dysregulation of miR-410-3p occurs in a tissue-speci c manner in different types of diseases. One study reported that miR-410-3p can protect chondrocytes from apoptosis by regulating NF-kB signaling pathway via targeting HMGB1 in osteoarthritis [10]. Additionally, previous studies have shown that miR-410-3p suppresses cytokine release from broblast-like synoviocytes by regulating NF-kB signaling in rheumatoid arthritis [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study in mice with osteoarthritis (OA), miR-410 was observed to be markedly downregulated in articular cartilage tissues, as well as in LPS-treated chondrocytes, in OA mice. While the upregulation of miR-410 markedly inhibited the expression of high mobility group box protein (HMGB)-1, a target gene of miR-410, as well as the activity of NF-κB and the production of pro-inflammatory cytokines such as IL-1β, IL-6, and TNF-α [176]. On the other hand, Wang et al reported that miR-410 expression levels were downregulated in synovial tissues and fibroblast-like synoviocytes (FLSs).…”
Section: Mir-410mentioning
confidence: 99%